Remission of Anti-laminin 332 Mucous Membrane Pemphigoid Associated with Non-small Cell Lung Cancer after Therapy with Rituximab and Intravenous Immunoglobulin - Evelyne Tarnowietzki; Thorsten Peters; Lea Kraus; Enno Schmidt; Karin Scharffetter-Kochanek (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)